TRADISI UPACARA MENUMBAI SIALANG (MENGAMBIL MADU LEBAH) DI KECAMATAN SUNGAI APIT KABUPATEN SIAK - Mia Novrianti; Isjoni Isjoni; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Tapping sialang is a tradition of taking honey bees in a sialang tree done 3 times in one year, its execution time at the dark moon. This tradition is a downward descending tradition of the ancestors who are still preserved. The purpose of this research is 1) to know the history of the origins of the traditional ceremony of sialang adi in the subdistrict of apit river siak district, 2) to know the process of the implementation of the tradition of tribal ceremony sialang in river apit districk siak regency, 3) to know the function of the tradition of tribal ceremony sialang in the local community's economic income, 3) to find out what efforts are made by local community leaders and community in preserving the tradition of tribal fringe ceremony in the district of Siak regency river. The method used in this research is the historical method of qualitative approach. Data obtained from the interviews are then analyzed in their own language. The location of the research is in the subdistrict of Siak regency river. The time of study began after the decree issued by the dean of faculty teacher and education science university riau. Data collection techniques used are observation and interview techniques. The results of the study provide us with the knowledge that there is a special technique in harvesting honey bees on the sialang tree so that the bees do not intercept in the process of harvesting the honey.Keywords: Tradition, Fringing Sialang